Plea Bargaining As A Reform of Criminal Procedural Law To Realize The Principle Of Swift, Simple, And Low-Cost Justice - Cavin George Ngilawane; Salvadoris Pieter; Mulyadi Alrianto Tajuddin (LUTUR Law Journal, 2025)
The Indonesian judicial system faces persistent challenges, including chronic case backlogs and severe prison overcrowding, which undermine the constitutional principle of swift, simple, and low-cost justice. This study explores the necessity of integrating Plea Bargaining into Indonesian criminal procedural law through the "Special Track" (Jalur Khusus) mechanism proposed in the Draft Criminal Procedure Code (RUU KUHAP). Employing normative legal research and a comparative approach—examining legal frameworks in the United States, England, and the Netherlands—the research identifies that Indonesia’s proposed model adopts a "pleas without bargains" framework. This model is intentionally designed to bypass corruptive negotiations while maintaining judicial control. The findings demonstrate that the Special Track streamlines the trial process by shifting ordinary examinations into abbreviated procedures for offenses carrying a maximum seven-year penalty, offering a mandatory sentence reduction of up to one-third. Furthermore, this study critically analyzes potential implementation hurdles, such as the risk of coerced confessions, the need for standardized judicial discretion, and the prevailing retributive legal culture in Indonesia. The research concludes that while the Special Track is a vital administrative tool for judicial efficiency, its success depends on rigorous judicial oversight to ensure that procedural speed does not compromise material justice or the defendant's fundamental rights.